2018
DOI: 10.1007/s00198-017-4356-x
|View full text |Cite
|
Sign up to set email alerts
|

Tocotrienol supplementation suppressed bone resorption and oxidative stress in postmenopausal osteopenic women: a 12-week randomized double-blinded placebo-controlled trial

Abstract: Tocotrienols and bone health of postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 39 publications
3
36
0
1
Order By: Relevance
“…Supplementation of annatto T3 (430 or 860 mg/day) for 12 weeks decreased bone marker levels (serum bone-specific alkaline phosphatase (BALP), urine N-terminal telopeptide (NTX), serum soluble RANKL and RANKL/OPG ratio) and oxidative stress biomarker (urinary 8-hydroxy-2 -deoxyguanosine (8-OHdG)) in postmenopausal women with osteopenia relative to the placebo group. These findings suggested that T3 exerted osteoprotective effects by suppressing bone remodeling regulators in postmenopausal women with osteopenia, which might be in part mediated by the inhibition of oxidative stress [168].…”
Section: Effects Of Tocotrienol On Osteoporosismentioning
confidence: 88%
See 1 more Smart Citation
“…Supplementation of annatto T3 (430 or 860 mg/day) for 12 weeks decreased bone marker levels (serum bone-specific alkaline phosphatase (BALP), urine N-terminal telopeptide (NTX), serum soluble RANKL and RANKL/OPG ratio) and oxidative stress biomarker (urinary 8-hydroxy-2 -deoxyguanosine (8-OHdG)) in postmenopausal women with osteopenia relative to the placebo group. These findings suggested that T3 exerted osteoprotective effects by suppressing bone remodeling regulators in postmenopausal women with osteopenia, which might be in part mediated by the inhibition of oxidative stress [168].…”
Section: Effects Of Tocotrienol On Osteoporosismentioning
confidence: 88%
“…Recently, a double-blinded placebo-controlled trial involving 89 postmenopausal women with osteopenia was conducted to investigate the effects of T3 on bone [168]. Supplementation of annatto T3 (430 or 860 mg/day) for 12 weeks decreased bone marker levels (serum bone-specific alkaline phosphatase (BALP), urine N-terminal telopeptide (NTX), serum soluble RANKL and RANKL/OPG ratio) and oxidative stress biomarker (urinary 8-hydroxy-2 -deoxyguanosine (8-OHdG)) in postmenopausal women with osteopenia relative to the placebo group.…”
Section: Effects Of Tocotrienol On Osteoporosismentioning
confidence: 99%
“…This δ-TT concentration was employed in the subsequent experiments. Since dietary supplementation of annatto seeds (consisting of 90% δ-TT and 10% γ-TT) exerted bone protective effects in postmenopausal women [24], we examined the ability of increasing γ-TT concentrations to counteract t-BHP-induced cytotoxicity. We found that γ-TT protects MC3T3-E1 cells against oxidative damage even if at a lesser extent than δ-TT ( Fig.…”
Section: Effects Of δ-Tt On Counteracting T-bhp-induced Oxidative Strmentioning
confidence: 99%
“…Clinical studies have reported that dietary supplementation of TTs extracted from annatto seeds (consisting of 90% δ-TT and 10% γ-TT) exerts a beneficial action on bone turnover in postmenopausal women. Interestingly, the positive action of TTs on bone is at least in part due to a suppression of oxidative stress [24].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there is not a single study yet to evaluate how TT supplementation affects gut microbiome in humans, particularly obese PMW. We previously reported that 12-week annatto-extracted TT supplementation suppressed bone resorption and oxidative stress in PMW with low bone mass 35. However, there is no study to evaluate how TT supplementation would affect obese PMW.…”
Section: Introductionmentioning
confidence: 99%